2023
DOI: 10.1001/jamanetworkopen.2023.12152
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Hypothermia, Cerebral Magnetic Resonance Biomarkers, and Outcomes in Neonates With Moderate or Severe Hypoxic-Ischemic Encephalopathy Born at Tertiary Care Centers vs Other Facilities

Sudhin Thayyil,
Paolo Montaldo,
Vaisakh Krishnan
et al.

Abstract: ImportanceThe association between place of birth and hypothermic neuroprotection after hypoxic-ischemic encephalopathy (HIE) in low- and middle-income countries (LMICs) is unknown.ObjectiveTo ascertain the association between place of birth and the efficacy of whole-body hypothermia for protection against brain injury measured by magnetic resonance (MR) biomarkers among neonates born at a tertiary care center (inborn) or other facilities (outborn).Design, Setting, and ParticipantsThis nested cohort study withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The administration of antipyretic steroids is another potential factor that has a substantial role in determining death rates. 23,24 CONCLUSION HT has not reduced, but may have increased, mortality in TBI patients in some high-quality studies. However, TBI patients with elevated ICP may benefit from hypothermia as therapy rather than as prophylaxis when initiated within 24 hours.…”
Section: Discussionmentioning
confidence: 98%
“…The administration of antipyretic steroids is another potential factor that has a substantial role in determining death rates. 23,24 CONCLUSION HT has not reduced, but may have increased, mortality in TBI patients in some high-quality studies. However, TBI patients with elevated ICP may benefit from hypothermia as therapy rather than as prophylaxis when initiated within 24 hours.…”
Section: Discussionmentioning
confidence: 98%
“…This might provide new insights for treating HIBD. Currently, hypothermia therapy is the only approved treatment method, but its high cost and uncertain prognostic effects remain a concern ( Ranjan and Gulati, 2023 ; Thayyil et al, 2023 ). Treatment starting within 6 h shows neuroprotective effects, posing a huge challenge for early diagnosis of HIBD.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Nonetheless, hypothermia was not neuroprotective, regardless of the duration of birth depression or birth acidosis 7 and place of birth. 6 It is not known whether the differential response to whole-body hypothermia between HICs and South Asia is associated with the underlying disease mechanisms. Whole-blood gene expression profile is increasingly used to characterize host responses in various infectious diseases, 8 , 9 , 10 , 11 including neonatal cytomegalovirus infections, 12 and in HIE wherein the gene profiles are different for healthy neonates vs those with sepsis.…”
Section: Introductionmentioning
confidence: 97%
“…However, the Hypothermia for Encephalopathy in Low-Income and Middle-Income Countries (HELIX) trial, the largest clinical trial of hypothermia in the world that was conducted in South Asia, reported that hypothermia did not reduce brain injury but increased mortality. Whole-body hypothermia was administered using servocontrolled devices in the HELIX trial, and attainment of the target temperature was earlier than in hypothermia trials in HICs . Nonetheless, hypothermia was not neuroprotective, regardless of the duration of birth depression or birth acidosis and place of birth .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation